“Cleansing” anatomical collections: The politics of removing specimens from German anatomical and medical collections 1988–92 - Weindling, Paul (Annals of anatomy, 2012)
In 1989–90 an intense debate erupted in the Federal Republic of Germany over the status of anatomical specimens from the period of National Socialism. Pressure was brought on the German universities and research institutes to remove body parts. The solution was deemed rapid burial of all specimens whose provenance was in doubt. A range of options was considered, and the eventual decision to bury cremated remains was deemed the best way to draw a line under an uncomfortable past of Nazi medical atrocities. The aim was to achieve closure on this issue by a rapid “cleansing” of collections. However, identification of victims was left unresolved amidst the heated debates at the time.